Mental wellbeing of higher education students in challenging times - Lazarewicz, Magdalena Anna; Moksnes, Unni Karin; Reidunsdatter, Randi Johansen; Wlodarczyk, Dorota (Frontiers in Public Health, 2025)
ObjectiveStudent age and starting higher education require adaptation to a new physical and psychosocial environment, making the time of studies a highly sensitive period. Current and future generations of students are also likely to face additional global stressors, which potentially exacerbate their mental wellbeing. The aim of the study was to investigate how higher education students' appraisal of the COVID-19 pandemic situation and of their personal resources predict mental wellbeing (anxiety and curiosity).MethodsThe study used cross-sectional data collected from 3,727 higher education students in an online survey conducted during the first wave of the COVID-19 pandemic.ResultsAfter controlling for a number of pandemic-related factors, all considered aspects of the pandemic situation appraisal and resources appraisal were significant predictors of anxiety and/or curiosity. The most important predictors of anxiety were sense of control, information stress, pandemic interest, and self-efficacy, and the most important predictors of curiosity were self-efficacy, health promoting behaviors, and sense of control. Tested models explained 61% of variance of anxiety and 36% of variance of curiosity.ConclusionAppraisal of own personal resources seems critical for both indicators of mental wellbeing. These results may significantly contribute to sufficient planning of mental-wellbeing oriented interventions for young adults in Higher Education.